Anatase nanotubes as an electrode material for Lithium-Ion batteries - Zakharova, Galina S.; Jähne, Carsten; Klingeler, Rüdiger (The journal of physical chemistry. C, Energy, materials, and catalysis, 2012)
Anatase TiO2 nanotubes were synthesized via the hydrothermal method followed by annealing at 500 °C in argon for 1 h. The phase structure, morphology, and composition were investigated in detail by means of X-ray diffraction, scanning and high-resolution transmission electron microscopy, infrared spectroscopy, and thermal analysis. The material consists of nanotubes with diameter of 10-15 nm and lengths of several hundred nanometers. The electrochemical properties were investigated by cyclic voltammetry and galvanostatic cycling. The data imply a first cycle irreversible capacity of 385 mAh/g, and capacities of 307 and 265 mAh/g after the second and 50th cycle, respectively, at C/10. The Coulombic efficiency of about 99% after cycle 50 implies excellent cycling stability. Hence anatase TiO2 nanotubes evidence great potential for usage in high-power lithium-ion batteries.